(untitled) (Ustozlar uchun, 2025)
Abstract: Error correction is one of the most debated yet essential aspects of language pedagogy. This study investigates how various error correction strategies influence the development of learner autonomy in English as a Foreign Language (EFL) contexts, with a particular focus on Uzbek classrooms. Through a combination of theoretical analysis and classroom-based observations, this paper explores the relationship between teachers’ corrective feedback, learners’ self-regulation, and the gradual emergence of autonomy in language learning. Findings indicate that when correction is handled reflectively and interactively, it promotes learners’ responsibility, self-monitoring, and confidence — key components of autonomous learning